Entamoeba gingivalis Causes Oral Inflammation and Tissue Destruction. (May 2020) - Bao, X.; Wiehe, R.; Dommisch, H.; Schaefer, A.S.
A metagenomics analysis showed a strongly increased frequency of the protozoan Entamoeba gingivalis in inflamed periodontal pockets, where it contributed the second-most abundant rRNA after human rRNA. This observation and the close biological relationship to Entamoeba histolytica, which causes inflammation and tissue destruction in the colon of predisposed individuals, raised our concern about its putative role in the pathogenesis of periodontitis. Histochemical staining of gingival epithelium inflamed from generalized severe chronic periodontitis visualized the presence of E. gingivalis in conjunction with abundant neutrophils. We showed that on disruption of the epithelial barrier, E. gingivalis invaded gingival tissue, where it moved and fed on host cells. We validated the frequency of E. gingivalis in 158 patients with periodontitis and healthy controls by polymerase chain reaction and microscopy. In the cases, we detected the parasite in 77% of inflamed periodontal sites and 22% of healthy sites; 15% of healthy oral cavities were colonized by E. gingivalis . In primary gingival epithelial cells, we demonstrated by quantitative real-time polymerase chain reaction that infection with E. gingivalis but not with the oral bacterial pathogen Porphyromonas gingivalis strongly upregulated the inflammatory cytokine IL8 (1, 900 fold, P = 2 × 10 –4 ) and the epithelial barrier gene MUC21 (8-fold, P = 7 × 10 –4 ). In gingival fibroblasts, we showed upregulation of the collagenase MMP 13 (11-fold, P = 3 × 10 –4 ). Direct contact of E. gingivalis to gingival epithelial cells inhibited cell proliferation. We indicated the strong virulence potential of E. gingivalis and showed that the mechanisms of tissue invasion and destruction are similar to the colonic protozoan parasite E. histolytica . In conjunction with abundant colonization of inflamed periodontal sites and the known resistance of Entamoeba species to neutrophils, antimicrobial peptides, and various antibiotics, our results raise the awareness of this protozoan as a potential and, to date, underrated microbial driver of destructive forms of periodontitis.